2006 Annual Report on Operations Evaluation - Independent Evaluation Group (Washington, DC: World Bank, 2012)
The 2006 Annual Report on Operations Evaluation (AROE) updates the actions taken since the 2004 and 2005 AROEs to strengthen the results focus in monitoring and evaluation (M&E). First, it analyzes the implications of managing for results on Bank operations. Second, it assesses the extent to which the Bank's M&E systems provide staff with the information they need to better manage for results. Third, the report evaluates products and services of the Independent Evaluation Group-World Bank (IEG-WB) as part of a continuous process of self-evaluation and assesses their quality, influence, and use among both internal and external audiences. The report also raises some unresolved issues for further consideration. Finally, it makes recommendations on how M&E can be strengthened to increase the World Bank's effectiveness.